Running scared - Skurzynski, Gloria; Ferguson, Alane (Washington, D.C. : National Geographic, 2002)
While lost in a tunnel at Carlsbad Cavern, thirteen-year- old Jack, eleven-year-old Ashley, and their eight-year-old foster brother, Sam, think bats and darkness are their worst problems, until they stumble across thieves.
740
Accelerated Reader AR
Keywords: Lost children -- Juvenile fiction; Bats -- Juvenile fiction; Foster home care -- Juvenile fiction; National parks and reserves -- Juvenile fiction; Mystery and detective stories; Carlsbad Caverns National Park (N.M.) -- Juvenile fiction